A subject-specific finite element musculoskeletal framework for mechanics analysis of a total knee replacement. (22nd August 2018) - Shu, Liming; Yamamoto, Ko; Yao, Jiang; Saraswat, Prabhav; Liu, Yao; Mitsuishi, Mamoru; Sugita, Naohiko
Abstract: Concurrent use of finite element (FE) and musculoskeletal (MS) modeling techniques is capable of considering the interactions between prosthetic mechanics and subject dynamics after a total knee replacement (TKR) surgery is performed. However, it still has not been performed in terms of favorable prediction accuracy and systematic experimental validation. In this study, we presented a methodology to develop a subject-specific FE-MS model of a human right lower extremity including the interactions among the subject-specific MS model, the knee joint model with ligament bundles, and the deformable FE prosthesis model. In order to evaluate its accuracy, the FE-MS model was compared with a traditional hinge-constraint MS model and experimentally verified over a gait cycle. Both models achieved good temporal agreement between the predicted muscle force and the electromyography results, though the magnitude on models is different. A higher predicted accuracy, quantified by the root-mean-square error ( RMSE ) and the squared Pearson correlation coefficient ( r 2 ), was found in the FE-MS model ( RMSE  = 177.2 N, r 2  = 0.90) when compared with the MS model ( RMSE  = 224.1 N, r 2  = 0.81) on the total tibiofemoral contact force. The contact mechanics, including the contact area, pressure, and stress were synchronously simulated, and the maximum contact pressure, 22.06 MPa, occurred on the medial side of the tibial insert without exceeding the yield strength of the ultra-high-molecular-weight polyethylene, 24.79 MPa. The approach outlines an accurate knee joint biomechanics analysis and provides an effective method of applying individualized prosthesis design and verification in TKR.